The Mediating Effect of Self-Esteem on the Association Between Minority Stress and Social Well-Being Among Indonesian Young Adult Gay Men and Lesbian Women: [Pengaruh Mediasi Self-Esteem Terhadap Hubungan Antara Minority Stress dan Kesejahteraan Sosial Pada Laki-Laki Gay dan Perempuan Lesbian Dewasa Muda] - Salim, Agnes Nugrawati; Halim, Magdalena Surjaningsih (Faculty of Psychology, Universitas Surabaya, 2024)
This study explores the correlation between minority stress, self-esteem, and social well-being among young adult gay men and lesbian women in Indonesia, by analyzing the mediating role of self-esteem on the correlation between minority stress and social well-being. Design utilized in this study is correlational design with mediation analysis. This study draws on a sample of 437 gay men and lesbian women (Mage = 24). The authors employed Spearman’s correlation and mediation analysis on the three measurement instruments. Results showed that all the measurement instruments correlated with each other significantly. Specifically, minority stress reduces self-esteem and in turn it will also lower the social well-being among young adult gay men and lesbian women in Indonesia. Moreover, the result also indicated that self-esteem have a partial mediating role on the relationship between minority stress and social well-being among young adult gay men and lesbian women. From the result of this study, it can be concluded that self-esteem is an important protective factor on gay men and lesbian women’s self-esteem. Therefore, the authors endorse a cultural shift to reduce minority stress among gay men and lesbian women in Indonesia. Additionally, organizations or mental health professionals may utilize self-esteem and social well-being as a mean for enhancing the mental health of Indonesian gay men and lesbian women. Studi ini mengeksplorasi korelasi antara minority stress, self-esteem, dan kesejahteraan sosial di kalangan laki-laki gay dan perempuan lesbian dewasa muda di Indonesia, dengan menganalisis peran mediasi self-esteem terhadap korelasi antara minority stress dan kesejahteraan sosial. Desain yang digunakan dalam studi ini adalah desain korelasional dengan analisis mediasi. Studi ini memiliki sampel 437 laki-laki gay dan perempuan lesbian (Mage = 24). Penulis menggunakan korelasi Spearman dan analisis mediasi pada ketiga instrumen pengukuran. Hasil studi menunjukkan bahwa seluruh instrumen pengukuran berkorelasi satu sama lain secara signifikan. Secara spesifik, minority stress menurunkan self-esteem, dan hal ini berakibat pada penurunan kesejahteraan sosial di kalangan laki-laki gay dan perempuan lesbian dewasa muda di Indonesia. Selain itu, hasil studi juga menunjukkan bahwa self-esteem memiliki peran mediasi parsial pada hubungan antara minority stress dan kesejahteraan sosial di kalangan laki-laki gay dan perempuan lesbian dewasa muda. Dari hasil studi ini, dapat disimpulkan bahwa self-esteem merupakan faktor pelindung yang penting terhadap self-esteem laki-laki gay dan perempuan lesbian. Maka dari itu, penulis mendukung perubahan budaya untuk mengurangi minority stress di kalangan laki-laki gay dan perempuan lesbian di Indonesia. Selain itu, organisasi atau layanan kesehatan mental profesional dapat memanfaatkan self-esteem dan kesejahteraan sosial sebagai sarana untuk meningkatkan kesehatan mental laki-laki gay dan perempuan lesbian di Indonesia.